Поняття інвестиційного потенціалу підприємства в контексті економічної безпеки - Вешкін, Є. П. (ХНУРЕ, 2024)
The main components of the enterprise's investment potential include: financial resources, human resources, technical and technological resources. The relationship between the use of the enterprise's investment potential and the state of its economic security is determined.
Keywords: інвестиційнмй потенціал; потенціал підприємства